2020
DOI: 10.3390/ijerph17134746
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Experiences, Knowledge, and Coping Behaviors of Nursing Students in Taiwan During Clinical Practicum

Abstract: Sexual harassment not only endangers nursing students’ physical and mental health but also considerably affects their future willingness to engage in the field of nursing. To identify experiences, knowledge, coping behaviors, and determinants of sexual harassment among nursing students during clinical practicum, this study conducted a cross-sectional survey where a structured self-report questionnaire was used. A total of 291 senior nursing students were recruited from four universities in Central Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 12 publications
0
26
0
2
Order By: Relevance
“…In a study in Ethiopia, among female pupils, it was found that sexual harassment mostly occurred in the schools, at 49.3 percent, followed by in classroom with 41.3 percent, and in the office at 19.7 percent [ 41 ]. Similarly, nursing students may experience sexual harassment during their clinical practicum, as a study reports more than one-fifth of them [ 42 ]. In an earlier study in Sweden, focusing on school environment, it was found that almost half of the female high school students who participated in the study (49 percent) identified sexual harassment as a problem in school and 15 percent believed this problem was serious [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Ethiopia, among female pupils, it was found that sexual harassment mostly occurred in the schools, at 49.3 percent, followed by in classroom with 41.3 percent, and in the office at 19.7 percent [ 41 ]. Similarly, nursing students may experience sexual harassment during their clinical practicum, as a study reports more than one-fifth of them [ 42 ]. In an earlier study in Sweden, focusing on school environment, it was found that almost half of the female high school students who participated in the study (49 percent) identified sexual harassment as a problem in school and 15 percent believed this problem was serious [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this same research, the typology of sexual violence is also manifested as relevant and student colleagues or nursing are pointed out as the main perpetrators, which shows that they are not prepared to solve the various circumstances of violence. Other related and notable facts were the high frequency of violence in the intermediate semesters16, in the classrooms, and in the clinical area, as in the case of Nayarit [27].…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, frequent sexual harassment of women was demonstrated, the perpetrators were the partners themselves, and the vulnerable population was in the initial and intermediate semesters, in mestizos, indigenous, Afro-descendants of the middle and lower middle class, foreign and homosexual [16]. More than a fifth of Taiwanese women were frequently sexually harassed in the clinical area [27] (Figure 1). In the Mexican environment, six research studies support the exercise of violence in nursing students at the high school level.…”
Section: Panorama Of the Prevalence Of Gender Violence In Nursing Stu...mentioning
confidence: 99%
“…Some patients make sexual advances during intimate care. Sexual harassment is defined as unwelcome sexual behaviour, including verbal, physical, psychological or visual forms (Chang, Tzeng & Teng 2020 ). Kahsay et al ( 2020 ) attest that sexual harassment of female nurses by male patients is prevalent; about 31% is physical and 40.8% psychological (verbal and visual).…”
Section: Discussionmentioning
confidence: 99%
“…The authors explain that nurses' exposure to harassment is because of their work bringing them to physical closeness with the patients. For nursing students, sexual harassment may lead to deterioration in physical and mental health(Chang et al 2020). Penile erection during intimate care is not well researched; most literature focuses on male patients' reproductive health dysfunctions and oncology problems.…”
mentioning
confidence: 99%